JUDGING PERFORMANCE IN GYMNASTICS: A MATTER OF MOTOR OR VISUAL EXPERIENCE? - Thomas Heinen; Pia M. Vinken; Konstantinos Velentzas (Science of Gymnastics Journal)
We addressed the question if laypeople with motor experience in gymnastics evaluate gymnastic performance similar to judges with only visual experience in the same domain. In addition we sought to explore the (biomechanical) sources of information that may account for the evaluation of gymnastics skills. We predict that laypeople rate handsprings on vault similar as expert judges and that gymnastics judges’ scores are related to time-discrete kinematic characteristics whereas laypeople’s scores are related to the form-aspect of the skill. 23 gymnastics judges and 23 laypeople rated handsprings on vault. Laypeoples’ scores were in average lower than gymnastics judges’ scores when judging handsprings. Laypeoples’ scores were predicted well by time-continuous kinematic parameters whereas judges’ scores were predicted well by time-discrete characteristics of the handsprings. We conclude, that judging in gymnastics can be facilitated by either own motor experience or specific visual experience.